1990
DOI: 10.1056/nejm199010253231703
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Clinical Aspects of the Hemolytic Uremic Syndrome in Minnesota

Abstract: This study provides evidence for an increase in the incidence of hemolytic uremic syndrome, which is probably related to an increased incidence of E. coli O157:H7 infections. Hemolytic uremic syndrome has become an important pediatric and public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
2
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(108 citation statements)
references
References 19 publications
4
97
2
3
Order By: Relevance
“…Indeed, salt loading protects against presumably nonthrombotic nephrotoxicity, such as that caused by amphotericin, 28 and isotonic saline prevents nephropathy caused by radiocontrast media better than does hypotonic saline. 29 It is interesting that unlike a Minnesota study that suggested that antibiotic administration was related to a milder course of HUS, 30 we detected no statistically significant association between antibiotic administration and development of either oligoanuria or nonoligoanuria. However, in our study, children who received antibiotics generally also received less intravenous sodium and fluids.…”
Section: Discussioncontrasting
confidence: 51%
“…Indeed, salt loading protects against presumably nonthrombotic nephrotoxicity, such as that caused by amphotericin, 28 and isotonic saline prevents nephropathy caused by radiocontrast media better than does hypotonic saline. 29 It is interesting that unlike a Minnesota study that suggested that antibiotic administration was related to a milder course of HUS, 30 we detected no statistically significant association between antibiotic administration and development of either oligoanuria or nonoligoanuria. However, in our study, children who received antibiotics generally also received less intravenous sodium and fluids.…”
Section: Discussioncontrasting
confidence: 51%
“…The large number of patients who needed simultaneous treatment was challenging, especially on resources, but the initial rate of complications was not unusual. Especially when looking at the published pediatric series from the US [5], Australia [6], Great Britain [7], and Germany [8], it seems that most pediatric patients with STEC O104:H4 HUS had a comparable course compared to historic controls. Two special features compared to the past, however, were the fact that patients were from a high socioeconomic status and that age at presentation was relatively high.…”
Section: Specific Pediatric Details In Comparison To Published Seriesmentioning
confidence: 99%
“…In population-based studies of HUS, age-specific incidence was highest among children Ͻ5 years of age, but these studies did not evaluate risk factors for progression of diarrhea or hemorrhagic colitis to HUS. [3][4][5][6] In some studies of children with E coli O157:H7 infection, girls were more likely than boys to develop HUS. 7,8 Patients who are infected with E coli O157:H7 and at the time of presentation to medical care have elevated white blood cell counts, fever, or bloody stools also have been noted to have a higher risk of progression to HUS than patients without these findings.…”
mentioning
confidence: 99%